Interferon‐Induced Transmembrane Proteins Mediate Viral Evasion in Acute and Chronic Hepatitis C Virus Infection. Issue 5 (21st June 2019) - Wrensch, Florian; Ligat, Gaëtan; Heydmann, Laura; Schuster, Catherine; Zeisel, Mirjam B.; Pessaux, Patrick; Habersetzer, François; King, Barnabas J.; Tarr, Alexander W.; Ball, Jonathan K.; Winkler, Michael; Pöhlmann, Stefan; et al.
Abstract : Although adaptive immune responses against hepatitis C virus (HCV) infection have been studied in great detail, the role of innate immunity in protection against HCV infection and immune evasion is only partially understood. Interferon‐induced transmembrane proteins (IFITMs) are innate effector proteins restricting host cell entry of many enveloped viruses, including HCV. However, the clinical impact of IFITMs on HCV immune escape remains to be determined. Here, we show that IFITMs promote viral escape from the neutralizing antibody (nAb) response in clinical cohorts of HCV‐infected patients. Using pseudoparticles bearing HCV envelope proteins from acutely infected patients, we show that HCV variants isolated preseroconversion are more sensitive to the antiviral activity of IFITMs than variants from patients isolated during chronic infection postseroconversion. Furthermore, HCV variants escaping nAb responses during liver transplantation exhibited a significantly higher resistance to IFITMs than variants that were eliminated posttransplantation. Gain‐of‐function and mechanistic studies revealed that IFITMs markedly enhance the antiviral activity of nAbs and suggest a cooperative effect of human monoclonal antibodies and IFITMs for antibody‐mediated neutralization driving the selection pressure in viral evasion. Perturbation studies with the IFITM antagonist amphotericin B revealed that modulation of membrane properties by IFITM proteins is responsible for the IFITM‐mediated blockade of viral entry and enhancement of antibody‐mediated neutralization. Conclusion: Our results indicate IFITM proteins as drivers of viral immune escape and antibody‐mediated HCV neutralization in acute and chronic HCV infection. These findings are of clinical relevance for the design of urgently needed HCV B‐cell vaccines and might help to increase the efficacy of future vaccine candidates.